INTEGRATING A.I TECHNOLOGY IN ARABIC LANGUAGE LEARNING: THE STRATEGIC ROLE OF THE LIBRARY AT ISLAMIC UNIVERSITY TRIBAKTI - Niqie, Mohamad Syah Rizal (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The Library of Islamic University Tribakti serves as a dynamic technical arm, complementing the institution's core functions in education, research, and community outreach. Functioning as a nexus of knowledge dissemination, it plays a pivotal role in providing access to resources and services essential for academic enrichment. Beyond traditional literacy support, the library embraces innovation by offering Artificial Intelligence (A.I.)-powered learning platforms. These cutting-edge tools, accessible through library-provided computer applications, represent a paradigm shift in educational technology. This research endeavors to delve into the library's multifaceted role in facilitating access to A.I.-driven learning media. By elucidating the integration of A.I. technologies within the library ecosystem, this study aims to underscore their transformative potential for enhancing student learning experiences. Furthermore, it seeks to explore the broader implications of A.I. integration in educational settings, shedding light on its impact on pedagogical approaches and learning outcomes. Through an interdisciplinary lens, this research contributes to the ongoing discourse on the intersection of technology and education, offering insights into the evolving landscape of contemporary learning environments